Mineralogy, geochemistry and origin of the Neoproterozoic Xaudum iron-formation in Botswana - Ntantiso, Mawande (Rhodes University, Faculty of Science, Department of Geology, 2020)
Banded iron-formations (BIF) formed in three different geological periods in the Earth's history, namely the Archean, Paleoproterozoic and Neoproterozoic. Each of these periods has a corresponding index BIF type attributed to them. The oldest is the Archean Algoma-type BIF which is typically dominated by smaller-volume BIF deposits associated with volcanic rocks and greenstone belts. The next is the volumetrically far more abundant Superior-type BIF of the Paleoproterozoic lacking any obvious volcanic relation. The youngest BIFs were deposited after a hiatus of a billion years in the Neoproterozoic and are believed to be genetically linked to Marinoan ice-age. The global re-introduction and distribution of BIF in the Neoproterozoic highlights a shift in the Earth's tectonics, climate, biosphere and ocean chemistry from the older Archean and Paleoproterozoic counterparts. Various models have been postulated by researchers in attempts to explain how Neoproterozoic iron-formations formed. In all the available models, the Snowball Earth Hypothesis initially proposed by Kirshvink (1992) is an overarching concept. In this study, four cores from the Neoproterozoic Xaudum iron-formation (XIF) in Ngamiland, northwest of Botswana, were sampled and analysed following a partnership between Postgraduate Research in Iron and Manganese Ore Resources (PRIMOR) and Tsodilo Resources Ltd. The study sets out to explore the mineralogy and chemistry of XIF in order to determine its origin, constrain the redox conditions in the paleo-basin, assess it in the context of other Neoproterozoic iron-formations and older Archean and Paleoproterozoic iron-formations, and inform metallurgical processing. The mineralogy of XIF consists of magnetite, quartz, amphibole, garnet, biotite and chlorite in decreasing abundance. This mineral assemblage is characteristic of medium grade metamorphosed iron-formations. Algoma and Superior-type BIFs which experienced late-diagenetic and very low-grade metamorphism have a complex mineral assemblage consisting of hematite, magnetite, quartz, and several carbonate (dolomite-ankerite series and siderite) and silicate phases (greenalite, riebeckite and stilpnomelane). The geochemical results show that XIF has higher Mn3O4 and Al2O3 average contents when compared to Algoma and Superior type BIF. The detrital components in XIF correlate with High Field Strength Elements (HFSE) suggesting increased delivery of siliciclastic material during deposition. This trend is comparable to other NIF deposits suggesting a global high input of siliciclastic material into Neoproterozoic paleodepositional environments. This trend is different from Archean and Paleoproterozoic BIF deposits which are close to pure chemical sediments lacking measurable detrital contributions. In the XIF, bulk-rock Mn3O4 and Al2O3 in drillcore SW have higher averages of 2.4 and 2.6 wt. % respectively, compared to the other three cores. The Mn3O4 shows a positive statistical relationship with Co, suggesting that Neoproterozoic oceans and atmosphere were possibly more oxic than in the Archean and Paleoproterozoic. The Mn3O4 shows an antithetic relationship with Fe2O3 suggesting that the paleobasin was chemically heterogeneous in terms of redox conditions, with Fe2O3 depositing presumably in deeper parts removed from a detrital source, and Mn3O4 depositing possibly more proximal to a paleo-shoreline in a shallower setting where there was higher delivery of siliciclastic material from the continent due to correspondingly higher Al2O3 and TiO2 contents. The REE patterns of XIF show positive-sloping trends of depletion in LREE and enrichment in HREE which resemble those of seawater. However, the REE slope becomes a lot flatter and resembles closer the signature of PAAS and adjacent diamictite facies, which agrees with the idea of high siliciclastic input in the paleobasin comparable to other NIF. XIF also appears to lack clear Ce or Eu anomalies. The lack of the former points to the oceans possibly not being oxic enough to drive the fractionation of Ce into Mn oxides like in the modern oceans, or that the Ce behaviour is obscured by the high siliciclastic input in XIF. Similarly, the lack of positive Eu anomaly shows a weak to absent hydrothermal signal into to modern shallow seawater where Fe and Si were sourced, or detritally derived REE contamination. Extensive weathering under hot and humid climate during glacial retreat is shown by the low K2O/Al2O3 ratios and high CIA values ranging from 80-99. Re-glaciation signifies the return of cold and arid and it is represented by high K2O/Al2O3 ratios and low CIA values ranging from 64-78. The previous genetic models of NIF by Klein (1993), Baldwin et al. (2012) and Lechte and Wallace (2015) provide an essential foundation for the development of a XIF genetic model. The genetic model of XIF proposes deposition on an open continental shelf characterized by a steady influx of detrital material. The seawater has been anoxic since the Paleoproterozoic and further induced by basin stagnation due to the ice covering the basin. Two overlapping oxidative stages are assumed for the precipitation of Fe and Mn across lateral redox gradients in the paleobasin. The exact oxidative pathways and mechanisms for the above processes remains unconstrained.
Keywords: Xaudum iron-formation; Iron ores -- Botswana; Formations (Geology) -- Botswana; Mineralogy -- Botswana; Paleoclimatology -- Proterozoic